Cover Feature: Fluorescence Properties of Flavin Semiquinone Radicals in Nitronate Monooxygenase (ChemBioChem 13/2019). (24th June 2019) - Su, Dan; Kabir, Mohammad Pabel; Orozco‐Gonzalez, Yoelvis; Gozem, Samer; Gadda, Giovanni
Abstract : The neutral flavin semiquinone radical stabilized in the active site of nitronate monooxygenase shows novel fluorescence behavior. It displays a broad UV–visible absorption spectrum in the near‐UV and visible light range and emits red fluorescence when excited with yellow and red light. Such fluorescence is not observed when using excitation light of a shorter wavelength. How the excitation‐wavelength‐dependent fluorescence behavior violates the Kasha–Vavilov rule is discussed in depth in the communication by G. Gadda et al. onpage 1646 in Issue 13, 2019 (DOI:10.1002/cbic.201900016 ).